The Effect of Snakes and Ladders Learning Media on Mathematics Learning Outcomes of Grade II Students of SDN 1 Kolaka - Patewa, Anna Thasya; Zulnuraini, Zulnuraini; Pendit, Sinta Satria Dewi; Rizal, Rizal; Guci, Ammar Abdullah Joni (FKIP - Universitas Riau, 2025)
This study aims to determine the effect of the Snakes and Ladders learning media on the mathematics learning outcomes of class II students at SDN 1 Kolaka. This research is a quantitative study with a pre-experimental design using a one-group pretest-posttest design. Data collection techniques were carried out through the administration of a pretest, treatment using the Snakes and Ladders media, and a posttest. The research instrument was a multiple-choice test that had been tested for validity and reliability using IBM SPSS Statistics version 27. The number of subjects in this study was 14 students. The results of descriptive statistical analysis showed that the average pretest score was 55, and the average posttest score was 85.36. The N-gain test results showed an increase in score of 0.7028, which falls into the high category, with a percentage of 70.28% categorized as fairly effective. The normality test showed that the data were normally distributed. Hypothesis testing using the Paired Sample T-test showed a significance value of 0.000 < 0.05, which indicates that there is a significant effect of using the Snakes and Ladders learning media on students’ mathematics learning outcomes. It can be concluded that the Snakes and Ladders learning media is effective and can affect the mathematics learning outcomes of class II students at SDN 1 Kolaka.